Development and appropriateness of a scoring method for International Classification of Functioning, Disabilities, and Health assessment in older patients with heart failure: a Delphi survey of expert panel in Japan. Issue 9 (17th September 2022) - Shiota, Shigehito; Kitagawa, Toshiro; Goto, Naoya; Fujisita, Hironori; Tamekuni, Yurika; Nakayama, Susumu; Mio, Naoki; Kanai, Kana; Naka, Makiko; Yamaguchi, Mizuho; Mochizuki, Mariko; Ochikubo, Hiroyuki; et al.
Abstract : Objective: The number of older patients with heart failure (HF) is increasing in Japan and has become a social problem. There is an urgent need to develop a comprehensive assessment methodology based on the common language of healthcare; the International Classification of Functioning, Disability and Health (ICF). The purpose of this study was to develop and confirm the appropriateness of a scoring methodology for 43 ICF categories in older people with HF. Design: Cross-sectional survey. We applied the RAND/University of California at Los Angeles (UCLA) Appropriateness Method with a modified Delphi method. Setting and participants: We included a panel of 26 multidisciplinary experts on HF care consisting of home physicians, cardiovascular physicians, care managers, nurses, physical therapists, a pharmacist, occupational therapist, nutritionist and a social worker. Measures: We conducted a literature review of ICF linking rules and developed a questionnaire on scoring methods linked to ICF categories in older people with HF. In the Delphi rounds, we sent the expert panel a questionnaire consisting of three questions for each of the 43 ICF categories. The expert panel responded to the questionnaire items on a 1 (very inappropriate) – 9 (very appropriate) Likert scale and repeated rounds until a consensus of 'Appropriate' and 'Agreement' was reached on all items. Results: A total of 21 panel members responded to all the Delphi rounds. In the first Delphi round, six question items in four ICF categories did not reach a consensus of 'Agreement', but the result of our modifications based on panel members' suggestions reached to a consensus of 'Appropriate' and 'Agreement' on all questions in the second Delphi round. Conclusion: The ICF-based scoring method for older people with HF developed in this study was found to be appropriate. Future work is needed to clarify whether comprehensive assessment and information sharing based on ICF contributes to preventing readmissions.